2012
DOI: 10.1002/ece3.217
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of phenotypic plasticity. X. Variation versus uncertainty

Abstract: Despite the apparent advantages of adaptive plasticity, it is not common. We examined the effects of variation and uncertainty on selection for plasticity using an individual-based computer simulation model. In the model, the environment consisted of a linear gradient of 50 demes with dispersal occurring either before or after selection. Individuals consisted of multiple loci whose phenotypic expression either are affected (plastic) or are not affected (nonplastic) by the environment. Typically, evolution occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
158
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(182 citation statements)
references
References 100 publications
15
158
1
3
Order By: Relevance
“…We found that fluctuating or rapid directional environmental change strongly selected for plastic genotypes. This result is in accordance with previous modelling approaches [22,41,42], especially when environmental fluctuations are modelled to act after development but before selection [43]. In our model, increased plasticity allowed genotypes to produce phenotypes better matching the changing environmental conditions at each generation, hence showing a high potential for rapid adaptation to new environments.…”
Section: Discussionsupporting
confidence: 90%
“…We found that fluctuating or rapid directional environmental change strongly selected for plastic genotypes. This result is in accordance with previous modelling approaches [22,41,42], especially when environmental fluctuations are modelled to act after development but before selection [43]. In our model, increased plasticity allowed genotypes to produce phenotypes better matching the changing environmental conditions at each generation, hence showing a high potential for rapid adaptation to new environments.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with theoretical predictions that increased adaptive plasticity is selectively favoured in populations and metapopulations that encounter variable environments ( [68,86,[104][105][106][107][108] and references therein). This particular selective property may lead to a positive evolutionary feedback for greater invasiveness in non-native taxa that have sufficiently broad norms of reaction to survive their initial introduction.…”
Section: (B) Plasticity and Evolutionary Potentialsupporting
confidence: 91%
“…This can be studied with individual-based simulations, as was done for ER without phenotypic plasticity by, e.g. Holt et al [102], and more recently for evolving plasticity (but without demography leading to extinction) by Scheiner & Holt [35].…”
Section: Perspectives and Conclusion (A) Other Topics Of Interestmentioning
confidence: 99%